2018
DOI: 10.1038/s41598-018-24882-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on histologic outcome of cervical intraepithelial neoplasia during observational management: results from large cohort, systematic review, meta-analysis

Abstract: Aim of this study was to investigate the histologic outcome of cervical intraepithelial neoplasia (CIN) during observational management. Consecutive women with histologically verified CIN and observational management were included. Histologic findings of initial and follow-up visits were collected and persistence, progression and regression rates at end of observational period were assessed. Uni- and multivariate analyses were performed. A systematic review of the literature and meta-analysis was performed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 39 publications
4
36
0
3
Order By: Relevance
“…Observational management should be considered for selected young patients with CIN. (19)(20)(21)(22) Prevention, early detection, and effective treatment of malignant tumors is one of the most important sections of modern medicine. The WHO guideline provides recommendations for screening and treatment of precancerous lesions to prevent CC.…”
Section: Resultsmentioning
confidence: 99%
“…Observational management should be considered for selected young patients with CIN. (19)(20)(21)(22) Prevention, early detection, and effective treatment of malignant tumors is one of the most important sections of modern medicine. The WHO guideline provides recommendations for screening and treatment of precancerous lesions to prevent CC.…”
Section: Resultsmentioning
confidence: 99%
“…For women younger than 25 years old, regardless of the level of cervical lesions, the rate of spontaneous regression was 1.4 times higher than that of women older than 50 years old [24]. Christine Bekos [25] obtained similar results; the proportion of women over 40 years old who experienced CIN progression was signi cantly higher than the proportion who were younger than 40 years, and for every extra 5 years of age, despite cervical lesion grades, the rate of spontaneous regression decreased by 21%. The results of this study showed that the average age for patients with SCC is signi cantly greater than that of CIN patients, suggesting that age is likely to be related to the progression of CIN.…”
Section: Discussionmentioning
confidence: 98%
“…For women younger than 25 years old, regardless of the level of cervical lesions, the rate of spontaneous regression was 1.4 times higher than that of women older than 50 years old [24]. Christine Bekos [25] obtained similar results; the proportion of women over 40 years old who experienced CIN progression was significantly higher than the proportion who were younger than 40 years, and for every extra 5 years of age, despite cervical lesion grades, the rate of spontaneous regression decreased by 21%. The results of this study showed that the average age for patients with SCC is significantly greater than that of CIN patients, suggesting that age is likely to be related to the progression of CIN.…”
Section: Clinical Factors Related To the Occurrence And Progression Omentioning
confidence: 98%